Adsorption performance of CNCl, NH3 and GB on modified graphene and the selectivity in O2 and N2 environment. (December 2022) - Zhu, Pengcheng; Tang, Fu; Wang, Shufen; Cao, Wei; Wang, Quan
Abstract: Two-dimensional materials have shown desirable application prospects in the field of gas sensing. Through the modification of graphene gas-sensitive materials, more efficient and sensitive gas sensors can be further developed. The use of metal atoms or oxygen-containing groups to modify graphene can improve its detection performance for gases. Modified-graphene could be selected as an excellent gas sensor for poisonous gas detection. In this work, adsorption systems of CNCl, NH3 and GB on metal doped graphene (Au, Ag, Cu and Fe) and graphene oxide were established by the using of density functional theory (DFT). The adsorption energy, charge transfer, DOS, PDOS and energy band of these adsorption systems were investigated. The gas adsorption strength and gas selectivity factor were introduced to evaluate the selectivity of each substrate to these harmful gases in O2 and N2 environments. The calculation shown strong adsorption between the metal-doped graphene and the adsorbed gas, with Fe-doped graphene having better adsorption performance. By contrast, between graphene oxide and the adsorbed gas, the effect was slight. Moreover, the energy band change of metal- doped graphene was more obvious than that of graphene oxide. In addition, under O2 and N2 environment, Au-doped graphene may have good selectivity for CNCl and NH3 while Ag-doped graphene may have good selectivity for GB. This result will provide reference for the development of graphene based gas sensors for CNCl, NH3 and GB. Graphical Abstract: ga1 Highlights: The metal-doped graphene shows good adsorption performance for CNCl, NH3 and GB compared with graphene oxide. Au doped graphene may have good gas selectivity for CNCl and NH3 under O2 and N2 environment. Ag doped graphene may have good gas selectivity for GB in O2 and N2 environment. These studies provide theoretical basis and new ideas for the research of modified graphene materials in harmful gas sensing.